Sustainable freshwater aquaculture in the EU and in Hungary - György Páczay (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2018)
There is a huge potential in freshwater aquaculture in the EU and in other countries in the World. As for the World food demand fish had the second highest consumption levels, at 27.9 percent in 2014. There will be a sharp increase in demand for fish and aquaculture products as the UN FAO projects around 9 billion people living our planet by 2050. The economy has already started its adaptation. While the World aquaculture production has increased from 7 to 82 million tonnes per year from 1990, there is no rise in the EU where we can observe a stagnation in production around 1.26 million tonnes annually. The EU has its potential: coastline around 68 thousand km, 500 thousand natural lakes, etc. Next to seawater aquaculture there are several freshwater fish species such as trout, carp or catfish whose production could be radically increased by investing, innovating and creating many new jobs in the freshwater sector. A small country, Hungary can show good examples in pond and intensive fish farming despite the country has not reached its full potential yet. The boost could be managed by increased grants and other incentives for investments, innovation, cooperation and promotion. The valuable ecological services which fish farmers provide year to year have also to be rewarded. So, let's start to act.